Today I am going to teach you how to solve a Multi-step equaton.
2(x-5)=5x+23, lets begin with this equation, first step we do is distibute, we are going to distribute whats inside the parenthesis.
2x-10=5x+23 you should get this answer, the next step is to combine like terms since there isn't anything to combine we are going to move to the next step which is to move the variable to the other side.
To move you variable to the other side you are going to subtract 2x from both sides. 5-2=3, you should get -10=3x+23
The next step to solving our multi-step equation is to move our constants to one side. We are going to move the -10 to the other side and the opposite of subtraction is addition. We are going to add 23+10=33. Our new equation is 3x=33.
The last step to do is divide, you are going to divide 33 to 3 and you should get 11, that means x=11.
This are all the steps to sloving a multi-step problem, hurray you did it!